Watermass structure in the western Indian Ocean- Part II: The spreading and transformation of the Persian Gulf water - PREMCHAND, K; SASTRY, JS; MURTY, CS (MAUSAM, 1986)
The spreading and the transformation of the Persian Gulf Watermass (POW) in the Arabian Sea and the Indian Ocean have been presented. The core layer of this watermass is found in the depth range of 250-300 m over most of the Arabian Sea with a tendency to deepen southwards. The salinity at the core decreases from 37.9%oin the Gulf of Oman to 35.1% coat the equatorial regions. Its spreading is found to be mainly towards the west-coast of India and southerly off the Indian coast. Owing to Intense vertical mixing, rapid transformation of this watermass takes place in the Gulf of Oman. Vertical mixing of this watermass with the Red Sea watermass along the Arabian coast given rise to an isohaline layer in the depth range of 250-800 m and this layer has been termed as ’Arabian Sea Intermediate Watermass’. The influence of PGW in the deeper layers is reflected by the relatively higher temperatures and salinities at all depths in the northern Arabian Sea. Downward fluxes of heat and salt as a result of vertical mixing are inferred all along the core of this watermass.